2019
DOI: 10.1177/1120700019832989
|View full text |Cite
|
Sign up to set email alerts
|

The rising use of total hip arthroplasty for femoral neck fractures in the United States

Abstract: Background: We examined the trends in the treatment of femoral neck fractures with arthroplasty in the United States from 2004–2013. Methods: We used the National Inpatient Sample database in conjunction with codes from the International Classification of Diseases, Ninth Revision, to identify patients receiving hemiarthroplasty (HA) or total hip arthroplasty (THA) for the treatment of closed femoral neck fracture from 2004–2013. We evaluated the trend of these 2 treatments along with demographics, comorbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…An increasing number of patients with FNF receive a total hip arthroplasty (THA) (64)(65)(66). A THA consists of replacing both the acetabulum and the femoral neck and head.…”
Section: Displaced Femoral Neck Fracturesmentioning
confidence: 99%
“…An increasing number of patients with FNF receive a total hip arthroplasty (THA) (64)(65)(66). A THA consists of replacing both the acetabulum and the femoral neck and head.…”
Section: Displaced Femoral Neck Fracturesmentioning
confidence: 99%
“…Hip fractures without surgery were not included because the clinical interest of the survival analysis is due to the fact that it is a criterion for deciding the type of surgical procedure or the patients with fractures in the trochanteric area in whom the surgical management is different. Partial arthroplasty, preferably cemented, is the most indicated option for those patients with a limited life expectancy, with poorer function and mobility, or with cognitive alterations 13 . In recent years there has been an increase in the use of total arthroplasty for the surgical treatment of femoral neck fractures 13 , but an analysis of results from the clinical and also the economic point of view is necessary to know in what type of patients its use is more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Partial arthroplasty, preferably cemented, is the most indicated option for those patients with a limited life expectancy, with poorer function and mobility, or with cognitive alterations 13 . In recent years there has been an increase in the use of total arthroplasty for the surgical treatment of femoral neck fractures 13 , but an analysis of results from the clinical and also the economic point of view is necessary to know in what type of patients its use is more efficient. Total arthroplasty is more expensive, requires a longer surgery time, is more aggressive for the patient and with a higher probability of postoperative anemia and the need for transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…6 Less is known about the economic impact of selecting cemented versus press-fit (non-cemented) implants in the US market. 11,12 Studies have demonstrated that the additional operative time and accessories used to achieve the cement technique result in a higher cost than when utilizing a pressfit construct. 13 Because there is little evidence to suggest superior clinical outcomes through contemporary implants and fixation methods, the choice of the device can result in cost savings without impacting the quality of care.…”
Section: Introductionmentioning
confidence: 99%